2004
DOI: 10.1002/ijc.20228
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways required for matrix metalloproteinase‐9 induction by betacellulin in head‐and‐neck squamous carcinoma cells

Abstract: The mechanisms by which c-erbB-dependent signaling contribute to the invasive potential of HNSCC remain to be fully elucidated. We have previously shown that c-erbB autocrine and/or paracrine stimulation upregulates MMP-9 but has no effect on the related gelatinase, MMP-2. BTC, a major c-erbB ligand, has the ability to efficiently activate all c-erbB receptors and to bind directly to EGFR and c-erbB

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Increased cellular invasion is often accompanied by increased activity of proteins that degrade the extracellular matrix such as members of the MMP family. In addition, the MAPK and PI3K pathways have been shown to regulate expression of MMP family members (31,37,38). Therefore, we assessed the activity and expression of several members of the MMP family in MCF7/PODXL and PC3/PODXL cells.…”
Section: Resultsmentioning
confidence: 99%
“…Increased cellular invasion is often accompanied by increased activity of proteins that degrade the extracellular matrix such as members of the MMP family. In addition, the MAPK and PI3K pathways have been shown to regulate expression of MMP family members (31,37,38). Therefore, we assessed the activity and expression of several members of the MMP family in MCF7/PODXL and PC3/PODXL cells.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical correlation between pERK expression and invasion can be reconciled at the molecular level through activated ERK induction of extracellular matrix-digesting enzymes, facilitating cell migration, and invasion into surrounding tissue. [48][49][50][51] Recently, it has been demonstrated that the invasive capacity of the human renal cell carcinoma cell line Caki-2 is substantially increased on…”
Section: Discussionmentioning
confidence: 99%
“…These studies support our immunohistochemical results, which showed decreased protein expression of MMP-9 after treatment with the EGFR inhibitor AEE788. Furthermore, other research has shown that blocking of phosphatidylinositol 3-kinase by selective inhibitors effectively inhibited betacellulin-enhanced MMP-9 expression in head and neck squamous cell carcinoma cells, indicating that phosphatidylinositol 3-kinase/Akt is required in this process (27,28). MMP-9 has a nuclear factor nB (NF-nB) binding site in its promoter region and, therefore, expression of MMP-9 is regulated by NF-nB transcriptional activity (28).…”
Section: Discussionmentioning
confidence: 99%